Editorial: Microbial services for sustainable agriculture - Rigobelo, Everlon Cid [UNESP] (2022)
Laboratory of Soil Microbiology Faculty of Agricultural and Veterinary Sciences Department of Agricultural Production Sciences São Paulo State University